2022
DOI: 10.3389/fcimb.2022.967493
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective potential of chimeric virus-like particles containing SARS-CoV-2 spike and H5N1 matrix 1 proteins

Abstract: Coronavirus Disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), has posed a constant threat to human beings and the world economy for more than two years. Vaccination is the first choice to control and prevent the pandemic. However, an effective SARS-CoV-2 vaccine against the virus infection is still needed. This study designed and prepared four kinds of virus-like particles (VLPs) using an insect expression system. Two constructs encoded wild-type SARS-CoV-2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…As shown in Figure 2C, Western blot analysis revealed that the S-HA and M1 proteins were incorporated into the VLPs with the correct molecular weight (S-HA, 174 kDa and M1, 25 kDa). However, the SHAM1 VLPs were slightly larger in size (~100-200 nm diameter), similar to previously engineered pseudotyped VLPs for both SARS-CoV-1 (~160 nm diameter) [42] and SARS-CoV-2 (~80-200 nm diameter) [44,45]. To examine if pseudotyping improves VLP spike yield, S protein quantification was performed as described above (Figure S1A).…”
Section: Pseudotyping Improves Sars-cov-2 Vlp Spike Yieldsupporting
confidence: 67%
See 2 more Smart Citations
“…As shown in Figure 2C, Western blot analysis revealed that the S-HA and M1 proteins were incorporated into the VLPs with the correct molecular weight (S-HA, 174 kDa and M1, 25 kDa). However, the SHAM1 VLPs were slightly larger in size (~100-200 nm diameter), similar to previously engineered pseudotyped VLPs for both SARS-CoV-1 (~160 nm diameter) [42] and SARS-CoV-2 (~80-200 nm diameter) [44,45]. To examine if pseudotyping improves VLP spike yield, S protein quantification was performed as described above (Figure S1A).…”
Section: Pseudotyping Improves Sars-cov-2 Vlp Spike Yieldsupporting
confidence: 67%
“…Pseudotyping using influenza proteins was previously employed for SARS-CoV-1 VLPs in Sf9 cells, leading to >twofold improvement in VLP spike yield (1 mg/L) [42] compared to that of SARS-CoV-1 SEM VLPs [43]. A similar strategy was more recently utilized for SARS-CoV-2 VLPs in mammalian [44] and Sf9 insect cells [33,45], though the VLP spike yields were not reported. To determine if pseudotyping similarly improves SARS-CoV-2 VLP spike yield, a baculovirus vector was created to express the SARS-CoV-2 S ectodomain (aa 1-1213) fused to the transmembrane (TM) and cytoplasmic tail (CT) domains of an H1N1 influenza HA protein (accession #NP_040980) in combination with the influenza matrix protein M1 (denoted SHAM1, Figure 2A).…”
Section: Pseudotyping Improves Sars-cov-2 Vlp Spike Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained cell-containing virus liquid was repeatedly frozen and thawed at −80°C for three times, and then centrifuged at 12,000 rpm, 4°C for 30 min to collect the virus supernatants liquid. For VLPs purification ( Chen et al, 2022 ), the virus supernatants were loaded onto gradient sucrose solution (60, 45, 30, 20, and 10%, from densest to lightest using 6 ml per layer) in 38.5 ml Beckman ultra-clear tubes (Beckman Coulter, United States) and centrifuged at 40,000 rpm, 4°C for 4 h. The target protein in 10–30% was collected, and transferred to the new Beckman ultra-clear tubes containing 10 ml PBS and centrifugated at 40,000 rpm, 4°C for 4 h. The VLPs pellets were resuspended in PBS, and the purity of VLPs proteins were analyzed using Western blot.…”
Section: Methodsmentioning
confidence: 99%
“…Using a similar approach, H5N1 avian influenza VLPs that express the codon-optimized matrix and SARS-CoV-2 S proteins were reported to induce both cellular and humoral immune responses in mice. Adjuvanting these baculoviral VLPs with CpG ensured that all of the immunized mice survived the challenge infection with minimum weight loss and a significant reduction in SARS-CoV-2 RNA copy numbers in the lungs [ 129 ].…”
Section: Sars-cov-2mentioning
confidence: 99%